Faktor-Faktor yang mempengaruhi Pola Tidur Anak yang di Rawat - Supriyono, Supriyono; Ani Yuniarti, Falasifah (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background : Rest and sleep is a basic requirement needed by everyone. To be able to function normally, then everyone needs rest and sleep. Under conditions of rest and sleep, the body's recovery process to restore the stamina to be in optimal condition. Patterns of rest and sleep well and regularly gives a nice effect on health. However in sickness, sleep patterns usually disturbed. Objective : To determine factors that cause changes in sleep patterns and identify factors the most dominant affect the changes in sleep patterns of school age children who were treated at the pediatric ward. Methods : The study design using approach cross sectional with a methods questionnaire and observation. For this study there were 34 populations from the subjection mean of school age children per month are admitted to the ward Anggrek period of December 1st, 2011 â February 29th, 2012. Samples in this study is the total sample. The data in this study will be analyzed using univariate, bivariate with chi-square test, and multivariate with regression linear test with level a significance of 95% and the value of p < 0,05. Result : There are no effect significant of variables Environmental, Stress Psychological and Consumption of Drugs on the sleep patterns of school age child who underwent inpatient Anggrekâs Ward RSUD Panembahan Senopati Bantul with F value at 1,025 with significant 0,396 (sig > 0,05). Of the three factors that affect the childâs sleep pattern of factors Environmental, Stress Psychological and Consumption of Drugs only contribution for 0,2% of the sleep patterns of school age child with Adjusted R-Squared value of 0,002. Conclusion : Factors Environmental, Stress Psychological, and Consumption of Drugs do not affect significantly and only contribution for 0,2% of the sleep patterns of school age child. Keywords : Hospitalization, Sleep Patterns, School Age Child